Slow journalism for a new digital audience. The case of Longform.org (2010-2015) - Albalad Aiguabella, José María (2015)
In the past five years, new digital projects that combine the narrative tradition of the New American Journalism with the technological innovation have been created in the USA newspaper industry. The article focuses on one of the most significant cases: Longform.org (2010), an aggregator of long-form pieces, with an excellent research and writing, that includes the best slow journalism of cyberspace and, besides, it offers a product tailored to the tastes and interests of each user. The study has a depth interview to the founder, Aaron Lammer, in the newsroom of New York, where the author did an informal observation as part of the analysis.